Waterborne pH responsive hydrogels: Synthesis, characterization and selective pH responsive behavior around physiological pH. (10th October 2019) - Avais, Mohd.; Chattopadhyay, Subrata
Abstract: pH responsive hydrogels, which selectively show highest swelling capacity around physiological pH (~7.4) compared to both acidic and basic pH, are not known. In the current work, such hydrogels are prepared using one pot synthetic approach by reacting branched PEI with an azetidinium based crosslinker in water. Swelling capacity of the hydrogels is studied to understand the influence of crosslinking density and pH. The swelling capacity (SC) of the hydrogels decreases with increasing crosslinking density as expected. Further swelling capacity shows an excellent pH responsive behavior which is selectively higher around physiological pH (~7.4), when compared to pH 4, 7, 9.2 and 12. Selective swelling behavior around physiological pH also expected to influence the pH responsive drug release kinetics. To study that, drug encapsulated hydrogels are prepared and their release kinetics is studied as a function of pH. Both swelling capacity and drug release have shown very similar pH responsive trend and selectively higher drug release was observed around pH 7.4. Graphical abstract: Image 1 Highlights: (1) pH responsive hydrogels are developed, which shows highest swelling capacity around physiological pH~ 7.4, compared to both acidic and basic medium. (2) Synthesis of hydrogels using green azetidinium-amine reactions in water. (3) Selective and controlled drug delivery at pH 7.4, compared to both acidic and basic medium.